The Chinese in the Philippine economy 1989-1941 - Kwok-Chu, Wong (Quezon City, Philippines : ADMU Press, 1999)
The book concludes by boldly asserting that, among the four elements that helped explain the Chinese success as a business community - the Philippine Context, the Chineseness factor, the sojourning mentality and entrepreneurship.
Part one : The Chinese in the Philippine Economy -- Part two : The Chinese way of Business in the Philippines.
Includes bibliographical references and index.
Keywords: ECONOMIC CONDITIONS